(y + z)³ ( i believe you were trying to do the expression to the power of 3)
(y + z)³ = (y + z)(y + z)(y + z)
Use the FOIL method:
(y + z)(y + z) = y² + yz + yz + z²
Simplify
y² + 2yz + z²
plug in the answer gotten back into the expression
(y² + 2yz + z²)(y + z)
FOIL again, distribute each number to the other.
y²(y) = y³
y(2yz) = 2y²z
y(z²) = yz²
y²(z) = y²z
2yz(z) = 2yz²
z(z²) = z³
2y²z + 2yz² + y³ + z³ + y²z + yz²
Simplify: add all like variables
2y²z + y²z = 3y²z
2yz² + yz² = 3yz²
3y²z + 3yz² + y³ + z³ is your answer, or <span>y^3 + 3y^2z + 3yz^2 + z^3
hope this helps</span>
Answer:
24
Step-by-step explanation:
Answer:
C = 0.65M+19.65
Step-by-step explanation:
Given the the standard charge S (in dollars) given by the function
S = 0.40M + 15.75, where M is the number of miles driven.
Also the insurance charge I (in dollars) is given by the function
I = 0.25M + 3.90
If C is the total charge (in dollars) for a rental that includes insurance, then:
C = S + I
Substitute the given function into the expression:
C = 0.40M + 15.75 + 0.25M + 3.90
Collect like terms
C = 0.40M+0.25M+15.75+3.90
C = 0.65M+19.65
<em>Hence an equation relating C to M is expressed as C = 0.65M+19.65</em>
Answer:no
Step-by-step explanation:
The lengths of 2 sides of a triangle cannot add up to be greater than the hypotenuse or the 3rd larger side :)
Answer:
The slope-intercept form is y=mx+b y = m x + b , where m is the slope and b is the y-intercept. Using the slope-intercept form, the slope is 3 .
Step-by-step explanation:
brainliest please